2019
DOI: 10.1017/s1368980019001939
|View full text |Cite
|
Sign up to set email alerts
|

National general truck drivers’ strike and food security in a Brazilian metropolis

Abstract: Objective:We analysed the impact of the national general truck drivers’ strike on the availability, variety and price of foods sold by a food supply centre.Design:Descriptive study using secondary data to examine the percentage change in the mean price of fruits, vegetables and eggs before, during and after the strike. The strike in Brazil lasted 10 d from 21 to 30 May 2018. The drivers were on strike in order to make diesel oil tax-free and to obtain better working conditions.Setting:The food supply centre, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…Access to food and FI has also been investigated at critical moments in the country, such as the 2014-2015 economic crisis 19 and, more recently, during the truck drivers' strike 20 and the COVID-19 pandemic with the closure of commercial establishments 21 . Researchers found that the Brazilian economic crisis of 2014-2015 was associated with a sharp increase in the prevalence of FI in the state of Alagoas 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to food and FI has also been investigated at critical moments in the country, such as the 2014-2015 economic crisis 19 and, more recently, during the truck drivers' strike 20 and the COVID-19 pandemic with the closure of commercial establishments 21 . Researchers found that the Brazilian economic crisis of 2014-2015 was associated with a sharp increase in the prevalence of FI in the state of Alagoas 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that the Brazilian economic crisis of 2014-2015 was associated with a sharp increase in the prevalence of FI in the state of Alagoas 19 . Conversely, the truck drivers' strike was associated with a reduction in the availability and variety of food and an increase in the prices of fruit and vegetables 20 . Strategies to combat the COVID-19 pandemic related to the closing of commercial establishments, in turn, may have reduced the demand for fresh food 21 .…”
Section: Discussionmentioning
confidence: 99%
“…O acesso a alimentos e à IA também tem sido investigado em momentos críticos do país, como na crise econômica de 2014-2015 19 e, mais recentemente, durante a greve dos caminhoneiros 20 e na pandemia da COVID-19 com o fechamento dos estabelecimentos comerciais 21 . Verificou--se que a crise econômica brasileira de 2014-2015 se associou ao aumento acentuado na prevalência de IA no estado de Alagoas 19 .…”
Section: Discussionunclassified
“…Verificou--se que a crise econômica brasileira de 2014-2015 se associou ao aumento acentuado na prevalência de IA no estado de Alagoas 19 . Já a greve dos caminhoneiros foi associada à redução da disponibilidade e variedade de alimentos e ao aumento dos preços dos hortifrutigranjeiros 20 . As estratégias de combate à pandemia de COVID-19 relacionadas ao fechamento dos estabelecimentos comerciais, por sua vez, podem ter reduzido a demanda por alimentos in natura 21 .…”
Section: Discussionunclassified
“…A atividade de trabalho dos profissionais motoristas de caminhão influencia direta ou indiretamente a vida da população, o que foi evidenciado pelas consequências de greves nacionais recentes (LOPES et al, 2019).…”
Section: Organização De Trabalho Dos Motoristas De Caminhãounclassified